2021
DOI: 10.1002/solr.202100287
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Energy Loss to Achieve High Open‐circuit Voltage and Efficiency by Coordinating Energy‐Level Matching in Sn–Pb Binary Perovskite Solar Cells

Abstract: Tin–lead (Sn–Pb) binary low‐bandgap perovskites are more environmentally friendly than conventional Pb‐based perovskites and promise to deliver high photovoltaic performance by constructing tandem solar cells. However, the energy‐level mismatch between functional layers and tremendous trap states in perovskite films make it challenging to reduce the high open‐circuit voltage (Voc) loss in Sn–Pb binary perovskite solar cells (PSCs). Herein, energy loss reduction at the hole collection interface in Sn–Pb binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…As a HTL, NiO x has been considered a promising material since it has shown improved device stability compared to other polymeric HTLs. 26,54,55 In the particular case of TLPSCs, there is an absence of in-depth photostability studies to offer insights on the performance of NiO x HTLs. To compare these results to state-of-the-art devices, we fabricated MAFA and CsFA cells with PEDOT:PSS as an alternative HTL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a HTL, NiO x has been considered a promising material since it has shown improved device stability compared to other polymeric HTLs. 26,54,55 In the particular case of TLPSCs, there is an absence of in-depth photostability studies to offer insights on the performance of NiO x HTLs. To compare these results to state-of-the-art devices, we fabricated MAFA and CsFA cells with PEDOT:PSS as an alternative HTL.…”
Section: Resultsmentioning
confidence: 99%
“…(23) Different approaches to minimize this issue include the removal of the HTL (23)(24)(25), or the use of other HTLs such as NiO x or PTAA. (26)(27)(28)(29) Another critical aspect of the device stability is the selection of the A-site cation, namely Cs, MA, and formamidinium (FA). Devices based on the typical MAFA double cation or the CsMAFA triple cation compositions have consistently retained >95% of their original PCE after 1000 hours under dark and inert conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Space charge limited current (SCLC) measurements were conducted to quantitatively calculate the trap density of hole-only devices with the structure of ITO/PEDOT: PSS/Perovskite/spiro-OMeTAD/Au. [12] As shown in Figure S9, the trap density of the device with BBMS treatment was 1.26 × 10 16 cm À 3 compared with that of 2.32 × 10 16 cm À 3 for the control device. This indicates that BBMS passivated the perovskite film, which is expected to be associated with the improved stability of the BBMS-treated devices.…”
mentioning
confidence: 88%
“…However, the open circuit voltage ( V oc ) loss is noticeably large when compared with that of the Pb PSC counterparts. To overcome this issue, various studies have identified the main factors that led to the V oc losses such as the mismatched alignment in the energy levels and high defect densities in the perovskite absorbers. In the literature, the mismatch in the energy levels was tackled via interfacial engineering by architecturally aligning the energy levels of the solar cell components or through the introduction of a passivation layer. , Meanwhile, defect densities that contributed to the major carrier recombination were rectified via additive engineering by incorporation of additives or dopants into the perovskite absorbers to stimulate a homogeneous and slow growth of perovskite crystals. , An exemplary work by Hu et al that incorporated a glycinium hydrochloride molecule as an additive into the SnPb precursor has yielded the highest efficiency of 23.6% for SnPb PSCs with an astonishing V oc of 0.91 V . The inclusion of glycinium cations has been able to improve the surface morphology and crystalline quality and decrease the number of traps and defects, which in turn enhanced the carrier lifetime and minimized V oc loss.…”
mentioning
confidence: 99%